The standing of state-controlled entities under the ICSID Convention: Two key considerations - Mark Feldman (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2012)
ICSID tribunals likely will need to address with greater frequency the fundamental issue of whether disputes arising from SCE investments fall within the scope of the ICSID Convention. To help preserve clear ICSID Convention boundaries – which exclude public foreign investment disputes between states – ICSID tribunals should consider not only the nature, but also the purpose, of SCE investments.
Keywords: 330